contribution à l'analyse des risques sanitaires liés aux intoxications alimentaires au maroc et élaboration et application d’une démarche intégrée haccp-opera, pour la maîtrise du risque chimique lié à l'opérateur, dans une sucrerie - HAFIDA RACHIDI (Faculté des Sciences et des Techniques, Béni Mellal - Doctorat ou Doctorat National, 2011)
In order to develop the satisfaction of staff and customer, the company must maintain his Commitment to the val-ues of sustainable development that are taken into account when developing a strategy for continuous improvement of the quality, safety and health work. The problem of food poisoning has become alarming in Morocco; actually, several illnesses due to alimentation were reported last years. Therefore, we in collaboration with the poison control center and pharmacovigilance are highlighting statistics on food poisoning in Morocco from 2001 to 2004. The study showed that the poisoning cases were high; they were 5943 including 11 deaths. Also, a recent study made by the Poison Control Center of Morocco (CAPM) about food poisoning showed that from cases which were reported to the center, from 1989 to 2008, only 17 896 of alimentation diseases have been declared with 59 deaths (CAPM, 2010 ). This is mainly due to non communi-cation of food poisoning, weakness in medical facilities, unconsciousness of citizens on the importance of risk com-munication ... Hence, a specific interest should be brought to enhance a respect of standards and regulations, to control and to improve continuously manufacturing processes with the deployment of a quality, safety and health (QSS). The second objective of our study was to focus on methods of controlling food hygiene in Moroccan food busi-nesses, especially, the HACCP system. Our study in 2007 showed that only 811 establishments and food companies are HACCP certified or approved by the competent Moroccan authorities, 10 certified under the HACCP repository SNIMA and 801 HACCP approved by the veterinary services of Agriculture Ministry and Marine Fisheries. Cur-rently, 891 food companies in Morocco are agree to HACCP by the national safety of food products (ONSSA) and from 100 units producing dairy products that operate at the national level, just 70 units are registered by ONSSA. Each dairy unit, registered by that office, has a HACCP system or in most cases a self-monitoring system based on HACCP principles. So that, in order to improve working conditions and to prevent accidents and functional diseases we are interested on the psychosocial factors and ergonomic conditions of work achievement. It was obvious that the improvement of these conditions can increase the productivity, product’s quality and level of safety and personnel‘s health. Also, we have assembled the HACCP method and OPERA for the identification and assessment of chemical risks linked to the operator. The combination of the two methods gave the HACCP-OPERA method. It provides a clear and easy methodology to develop a safety plan and create a state of mind "quality, safety and health" in the company. It minimizes the multiplicity of references adopted by the food company to manage the risks associated with the product and the operator. It helps, therefore minimizing the cost and the frequency of training and awareness actions. This methodology has been applied successfully by our team in a laboratory for quality control of a sugar factory in Mo-rocco, to manage chemical risks and demonstrate the reliability and flexibility of its application. The result showed that the risks were significant and have a strong impact on health through the manipulation of certain chemical prod-uct. These can cause accidents and diseases, if the exposure was unacceptable and with little preventive measures. In general, the Moroccan company must be fully aware of its responsibilities of the risks to the consumer, health and safety of all persons affected by its activities. Currently, the management system of health and safety is included into the system of quality management. This system requires communication, coordination and supervision. Similarly, management should implement perfectly good practices in health and safety and promote awareness of all company staff.
Keywords: Risk Analysis; Health risk associated with food poisoning; Occupational hazard; Chemical risk; Quality; Health; Safety; HACCP; OPERA; Food Industry.; 1. Natural Sciences; 1.6 Biological sciences